The isle of France - Lopes, Paulo Roberto Masella (MATRIZes, 2007)
The reading of this book follow the history of Structuralism exploring it from layers in which stands the subject fields, the educational institutions, the magazines, the characters and the works that come out in the fifties, shake the sixties and have repercussions until nowadays. Layers that certainly blend together, creating nodules, accumulation points, that make evident the historical nature of each paradigm whose perception of credibility is assured through statements caught from its main characters allowing them the necessary critical distance to evaluate and review their positions and, for the reader, to follow the ruptures, the inflexions, the refluxes and idiosyncrasies of this history.